The Association between Vitamin D and Lipid Profile among Healthy Malay Adults in K ota Bharu, Malaysia (Bangladesh Journal of Medical Science, 2024)
Background:The effect of vitamin D in regulating lipid profiles is one of the proposed mechanisms for the association between vitamin D deficiency and cardiovascular heart disease (CHD). However, the relationship between vitamin D status and lipid profiles remained unclear.Objective: The objective of this study is to evaluate the association of vitamin D status on serum lipids among healthy adults.Material and Methods: This is cross-sectional study, involving 120 healthy adults with age of 18-50 years from the Malay adult in Kota Bharu, Malaysia which were selected via random sampling. To decrease the seasonal variability, the study was conducted within 2 months, between July and August 2015. Serum 25(OH)D, serum parathyroid hormone (PTH), serum triglycerides (TG), serum total cholesterol (TC), serum low density lipoprotein cholesterol (LDL-C) and serum high density lipoprotein cholesterol (HDL-C), fasting blood sugar (FBS) and serum insulin were measured.Results: The mean serum 25(OH) D was 23.50 ± 8.74 nmol/L. Based on the definition of vitamin D deficiency as serum 25(OH)D less than 30mmol/L, the proportion of vitamin D deficiency among our study subjects was 76.7%. Our data revealed that serum 25(OH) D had significant inverse association with HDL-C and significant positive association with TC, TG and LDL-C.Conclusions: Our study shows highly prevalence of vitamin D deficient among healthy Malay adult population in Kota Bharu, Malaysia. Serum 25(OH) D was positively associated with TC, TG and LDL-C and negatively associated with HDL-C. Perhaps optimizing the level of vitamin D might improve the lipid profiles among healthy Malay adults.Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 214-220